2020
DOI: 10.3390/ijms21072377
|View full text |Cite
|
Sign up to set email alerts
|

Array-Based Screening of Silver Nanoparticle Mineralization Peptides

Abstract: The use of biomolecules in nanomaterial synthesis has received increasing attention, because they can function as a medium to produce inorganic materials in ambient conditions. Short peptides are putative ligands that interact with metallic surfaces, as they have the potential to control the synthesis of nanoscale materials. Silver nanoparticle (AgNP) mineralization using peptides has been investigated; however, further comprehensive analysis must be carried out, because the design of peptide mediated-AgNP pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Afterward, Tanaka et al employed an array comprising 200 spot synthesis-based peptides and broadly evaluated the Ag NP mineralization activity of each peptide. 139 The size and morphology of the peptide-mineralized Ag NPs depend on the sequence of the peptide.…”
Section: Synthesis Of Mineralized Nanomaterials By Self-assembling Pe...mentioning
confidence: 99%
“…Afterward, Tanaka et al employed an array comprising 200 spot synthesis-based peptides and broadly evaluated the Ag NP mineralization activity of each peptide. 139 The size and morphology of the peptide-mineralized Ag NPs depend on the sequence of the peptide.…”
Section: Synthesis Of Mineralized Nanomaterials By Self-assembling Pe...mentioning
confidence: 99%
“…Tanaka et al 3 reviewed several novel properties that happen when the dimensions of solid material shrunk to the point of no return comprise tens to a few thousand atoms. Due to their specific electrical and optical properties, nanostructured deposition plays now a crucial role in several science and technology materials.…”
Section: Introductionmentioning
confidence: 99%
“…After a close review of the literary works 3,17 on the deposition of gold films, showed that the depositions of gold nanostructured materials on different alloys have received a little bit of attention. Furthermore, the study of the literature indicates that few works have been used Ni-Cr-Mo alloy substrate for depositions of gold thin films nanostructure to produce biocorrosion resistant materials for biological, medicinal, and dental applications.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental procedures are relatively simple and use inexpensive reagents and equipment, with a wide range of choices for library design; but most importantly, each SPOT can be individually designed and probed, so analysis of each sequence can be obtained for a deeper understanding and evaluation of the binding process. Previously, SPOT synthesis has been used for a wide variety of applications such as mapping of epitopes for antibody binding, protein-peptide recognition, enzyme specificity, and identifying peptides for cell adhesion, , and most recently, we have led the innovation of using the method to explore the interactions between peptides and inorganic materials. …”
Section: Introductionmentioning
confidence: 99%